Biodegradation of blend films PVA/PVC, PVA/PCL in soil and soil with landfill leachate - Campos, Adriana de [UNESP]; Marconato, José Carlos [UNESP]; Martins-Franchetti, Sandra Mara [UNESP] (Brazilian Archives of Biology and Technology, 2011)
This study investigated the biodegradation of blends films of poly(vinyl alcohol)/poly(vinyl chloride) (PVA/PVC) and poly(vinyl alcohol)/poly(caprolactone) (PVA/PCL) blends films prepared with dimethylformamide under a variety of conditions by respirometry, spectrophotometry (FTIR), scanning electron microscopy (SEM), and contact angle. The films were buried in the garden soil and in the soil mixed with the landfill leachate for 120 days at 28ºC. Significant levels of biodegradation were achieved in fairly short incubation times in the soil. The results indicated that PVA was the most biodegradable film in the soil and in the soil with the leachate.
Keywords: synthetic polymers; biodegradable polymers; soil; poly; poly; poly